Conversational Implicatures in “Stranger Things Season 1 Episode 1” Movie Series: Pragmatics Study - Zulfa Rahmadita Rachman; Heri Heryono (Budapest International Research and Critics University, 2022)
This study focuses on the conversational implicature in Stranger Things Season 1 Episode 1. It aims to analyze the types of conversational implicature and the reasons why the implicature occur spoken by the casts in the movie series. There are two types of conversational implicature in the movie series. Particularized conversational implicature and generalized conversational implicature. This research used descriptive qualitative method and obtained 9 particularized conversational implicature, and 22 generalized conversational implicature. The result of the research showed that in particularized implicature there are violations against maxim of relation (11.1%), maxim of manner (33,3%), maxim of quality (11.1%), and maxim of quantity (44.4%). Meanwhile, in generalized implicature, there are indefinite implicature (54.5%) and scalar implicature (36.3%). In addition, the reasons of conversational implicature are found, those are teasing, refusing, hurting, apologizing, convincing, wishing, caring, showing arrogance, disappointment and anger, reminding, informing, guessing, and self-defending.